BIOCHEMICAL CHANGES IN THE LIVER OF A FRESHWATER TELEOST, HETEROPNEUSTES FOSSILIS (BLOCH) EXPOSED TO ROGOR - DIXIT, YOGESH BABU; SAXENA, K.K.; CHAUHAN, SHALINI; DUBEY, A.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
When the catfish, Heteropneustes fossilis was exposed to a sublethal concentration of Rogor (10 ppm) for 48 days, the protein content decreased, whereas the Specific activities of acid phosphatase (ACP) and succinate dehydrogenase (SDH) showed an increased initially. However, a temporary recovery was observed between the second and third weeks of exposure. Thereafter the animals were released to normal water for 24 days. But they did not show any sign of recovery during this period.